2013
DOI: 10.1080/10550887.2013.824333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of QTc Interval Prolongation for Patients in Methadone Versus Buprenorphine Maintenance Treatment: A 5-Year Follow-Up

Abstract: The authors investigated whether patients receiving buprenorphine maintenance treatment (BMT) will have corrected QT (QTc) prolongation after taking buprenorphine for an extended period of time. They also compared QTc prolongation for patients in methadone maintenance treatment (MMT) versus BMT to determine which medication is the better option for patients with heart disease. A retrospective chart review study of 73 patients in BMT and 55 patients in MMT was performed. A linear regression model with a one-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…Supporting this conclusion was another study on 73 patients on BMT and 55 patients on MMT. In this study, Fareed et al [32] compared QTc prolongation in both groups over a 5-year period; their results demonstrated that unlike methadone, buprenorphine has no significant effect on QTc prolongation and is a safer drug for OMT than methadone. Also in 12 patients who had QT prolongation and ventricular arrhythmia due to methadone, changing methadone to buprenorphine in 3 of them made the QT interval normal and augmented the preference for buprenorphine over methadone [33].…”
Section: Prolongation Of Qt Interval and Ventricular Arrhythmiamentioning
confidence: 99%
“…Supporting this conclusion was another study on 73 patients on BMT and 55 patients on MMT. In this study, Fareed et al [32] compared QTc prolongation in both groups over a 5-year period; their results demonstrated that unlike methadone, buprenorphine has no significant effect on QTc prolongation and is a safer drug for OMT than methadone. Also in 12 patients who had QT prolongation and ventricular arrhythmia due to methadone, changing methadone to buprenorphine in 3 of them made the QT interval normal and augmented the preference for buprenorphine over methadone [33].…”
Section: Prolongation Of Qt Interval and Ventricular Arrhythmiamentioning
confidence: 99%
“…[43][44][45] Regarding adverse events, only a minor effect on corrected QT (QTc) interval duration has been reported with therapeutic doses of buprenorphine-naloxone, without proarrhythmic effects. 46,47 Conversely, methadone can increase the risk of a rare but fatal ventricular arrhythmia (torsades de pointes) because of its substantial QT-prolonging effects, especially at higher doses. 47 Case series have reported that transitioning patients taking methadone who were experiencing torsades de pointes to buprenorphine corrected the condition.…”
Section: Disadvantagesmentioning
confidence: 99%
“…Because QT prolongation can also be contributed by the methadone per se or HCV infection [7][8][9][10], we further verified the role of IP-10 on QTc through intraperitoneal injection of IP-10 (100 ng/g) to mice. The results showed that IP-10 did cause a significant increase in current QTc (data not shown).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 88%